Spatial variability of soil salinity and plant growth in the Sungai Besar coastline mangroves - Randhawa, Ne’ryez Singh (2017)
Mangrove forest plays an important part in our ecosystems. The most notable function of the mangroves is to provide protection along the coastlines. But due to the drastic decrease in population over the years, it is vital to conserve this unique species. UPM, along with their partners in FRIM, are collaborating to come up with a spatial variability map of the mangroves forest in Sungai Besar, Selangor. The map is created using parameters such as soil salinity and plant health. An area of 80m x 10m, with 40 quadrants within it, was formed. The soil salinity are measured in terms of electrical conductivity (EC). Soil samples from each quadrant was taken to analyze the EC at 2 different depths (0-15 cm and 15-30cm). Besides that, the chlorophyll content and girth (cm) of a random mangrove tree inside each quadrant is taken to measure plant growth. The samples are taken to UPM for labaratory analysis. Once all the data is formed, softwares such as GS+ and Surfer 8 (Golden Software) was used to analyze the data and come up with the spatial variability map. The results indicated that the middle of the sample plot are in better conditions, as compared to the sides and edges. This can accelerate site-specific management and save time and cost in terms of rapid assessment of the general health of the mangrove forest. Replication of similar experiments can also be conducted in the coastlines of Peninsular Malaysia for better utilization of resources based on site specific management.